(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Implants are an effective way to restore missing teeth; however, in some cases, implant removal may become necessary. One of the methods used for implant removal is the use of a bone trephine. This method is typically applied in situations where traditional extraction methods do not yield the desired result. This article provides a detailed review of the indications for implant removal, the technique of the procedure using a trephine, possible complications, and ways to prevent them.